Pengaruh Keselamatan Kesehatan K3 dan Jam Kerja Terhadap Kinerja Personil PKP-PK - Muhamad Zaki Aryatama; Muhammad Ananda Jumanka; Nunuk praptiningsih (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
This study aims to determine the influence of Occupational Health and Safety (OHS) and working hours on the performance of PKP-PK personnel. In this research, 77 respondents from PKP-PK personnel were interviewed to collect data on indicators related to the research variables and the selected sample population. The data were analyzed descriptively using IBM Statistics SPSS 20 for Windows. The results showed that Occupational Health and Safety (OHS) and working hours have a positive and significant impact on the performance of PKP-PK personnel. Occupational Health and Safety (OHS) positively and significantly influences the performance of PKP-PK personnel, with a coefficient of. Working hours also have a positive and significant effect on the performance of PKP-PK personnel. Thus, this study indicates that Occupational Health and Safety (OHS) and working hours play an important role in improving the performance of PKP-PK personnel. Companies must ensure appropriate occupational health and safety and working hours to enhance the performance of PKP-PK personnel.